DINAMIKA KONFIGURASI POLITIK TERHADAP KARAKTER PRODUK HUKUM ERA PEMERINTAHAN DEMOKRASI DI INDONESIA - Peggy Dian Septi Nur Anggraini; Wardah Yuspin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The history of political configurations appears to be alternating between democratic and authoritarian political configurations. Likewise, the character of the legal product produced is responsive or autonomous with repressive or conservative or orthodox character. The resulting legal product is a reflection of the political configuration that gave birth to it. The purpose of this research is to know the history of the development of political configuration on the character of Indonesian legal products. This type of research is normative showing that politics is influential in Indonesia's democratic system. The development of the political vision of the community will determine the character of the legal product. A regime that shows that it is more responsive and aspirational for the legal products it produces will create a more democratic life of the nation and state. Period I 1945-1959 During the Liberal Democratic Revolution, the political configuration was democratic, the character of legal products was responsive, the role of political parties as parliaments was very prominent. Period II 1959-1966 During the Old Order of Guided Democracy or Parliamentary political configuration, the character of orthodox legal products, there were deviations from constitutional democracy which showed people's democracy. Period III 1966-1998 The New Order period of Pancasila Democracy was configured with authoritarian politics with the character of orthodox legal products, constitutional democracy, namely Pancasila, with a prominent presidential system. Period IV 1998 The Constitutional Democratic Reform Period has a democratic political configuration, with the character of responsive legal products, the hope of upholding a democratic system of political freedom.